Machinability of soda lime glass in high speed end milling - Konneh, Mohamed; Bagum, Mst. Nasima; Mohamed Ariff, Tasnim Firdaus; Yeakub Ali, Mohammad (IOP Publishing, 2017)
Ductile regime machining can produce crack free surface on brittle material under certain controlled cutting conditions. Although end milling is a versatile process, it has not been frequently applied for machining soda lime glass. The brittle nature of the soda lime glass makes the machining difficult. Soda lime glass is a strain rate and temperature sensitive material. Therefore, high speed machining can be beneficiary to achieve ductile surface with low roughness. Hence, proper combination of cutting parameters needs to identify. In this paper, the effects of cutting parameters such as spindle speed, feed rate and depth cut on the surface roughness parameters Ra, Rq and Rt are investigated to assess machinability of soda lime glass during high-speed end milling. Regression models are generated and process parameters are optimized using the Central Composite Design (CCD) of Response Surface Methodology (RSM). The uncoated tungsten carbide tool was used to conduct milling operation. Experimental verification of optimal condition, spindle speed 40,000 rpm, feed rate 10 mm/min and depth of cut 34 μm confirmed that ductile surface with Ra, Rq and Rt of 0.33μm, 0.49μm and 6.59 μm respectively possible to achieve.